Populism in Latin America: Old and new populisms in Argentina and Brazil - Grigera, Juan Francisco (2017)
There has been a renewed interest in populism in Latin America, sparked by the social mobilization against neoliberalism usually referred to as the ‘Pink Tide’. Governments brought to power by the Pink Tide have been successful in reconstructing the conditions of capital accumulation as well as incorporating a new set of social movement demands. This article puts forward an interpretation of ‘Pink Tide neopopulism’ based on a political economy approach. It argues that the two factors of a crisis of neoliberalism in the region and the existence of social movements with unmet demands are not enough to explain the rise and demise of populism. The commodity boom needs to be added as an enabling condition for these transformations. By revisiting the debate in Latin America and proposing a different reading, the article redefines an overloaded term and provides a new analytical viewpoint from which to understand the ‘historical task’ of populism in Brazil and Argentina.